A simple, switchable pili‐labelling method by plasmid‐based replacement of pilin - Jingchao Zhang; Shubin Li; Tao Sun; Yiwu Zong; Weiwen Zhang; Kun Zhao (Environmental Microbiology, 2021)
Summary Labelling of Type IV pili (TFP) can greatly improve our understanding of the pivotal roles of TFP in a variety of bacterial activities including motility, surface sensing and DNA‐uptake etc. Here we show a simple and switchable pili‐labelling method by plasmid‐based inducible replacement of PilA without genetic modification in bacterial genome employed by complicated methods. Using this method, we characterized pili morphology and twitching motility of Pseudomonas aeruginosa in details. More importantly, we demonstrate its application in studying the replenishment dynamics of pilin pool of P . aeruginosa .